2021
DOI: 10.1200/op.20.01078
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Virtual Multidisciplinary Sarcoma Case Conference on Treatment Plan and Survival in a Large Integrated Healthcare System

Abstract: PURPOSE: Quantifying the impact of a multidisciplinary cancer case conference on patient outcome and care quality remains challenging. PATIENTS AND METHODS: We prospectively investigated the impact of our virtual multidisciplinary sarcoma case conference (VMSCC) on treatment plan in patients presented to the VMSCC from July to October 2020 (prospective cohort) and retrospectively in patients with metastatic or locally advanced high-grade soft-tissue sarcoma (STS) reviewed in the VMSCC in 2016 and 2017 (high-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“… 9 Virtual MTBs have been adapted by various specialties evaluating lung cancer, breast cancer, gastrointestinal cancers, lymphoma, and head, and neck cancer. 8 , 9 , 10 , 11 , 12 , 13 The virtual MTB plays an important role in changing management. A study of the multidisciplinary lymphoma virtual tumor board demonstrated changes in radiologic interpretation (1.9%), pathologic diagnosis (9.4%), and clinical management (30%).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 9 Virtual MTBs have been adapted by various specialties evaluating lung cancer, breast cancer, gastrointestinal cancers, lymphoma, and head, and neck cancer. 8 , 9 , 10 , 11 , 12 , 13 The virtual MTB plays an important role in changing management. A study of the multidisciplinary lymphoma virtual tumor board demonstrated changes in radiologic interpretation (1.9%), pathologic diagnosis (9.4%), and clinical management (30%).…”
mentioning
confidence: 99%
“…A 6‐month survey of participants in the lung cancer virtual MTB found that 95% believed the virtual MTB to be feasible and acceptable as well as impactful with regards to optimizing the flow of clinical information (91%), equity of care (96%) and specialist collaboration (88%) 9 . Virtual MTBs have been adapted by various specialties evaluating lung cancer, breast cancer, gastrointestinal cancers, lymphoma, and head, and neck cancer 8‐13 . The virtual MTB plays an important role in changing management.…”
mentioning
confidence: 99%
“…As a positive outcome of the COVID-19 pandemic, telehealth has made virtual collaboration more attainable than ever, allowing the expansions of existing medical networks via online communication. In previous studies of sarcoma MTBs that moved to an online platform as a result of the pandemic, there was no perceived difference in quality of discussion compared to in-person meetings [ 31 ], while also having no measurable effect on overall survival [ 32 ]. The potential impact of utilizing technology to create virtual MTBs, which connect single-institution or single-network MTBs into one large MTB, could change our entire existing framework of sarcoma care.…”
Section: Discussionmentioning
confidence: 99%
“…As one option with some similarities to AccessHope, Meyer et al 10 describe their experience with an asynchronous patient-initiated second opinion service (Best Doctors) covering all aspects of medicine that included 588 patients with hematology or oncology diagnoses, with opinions in this subset estimated to have moderate or major clinical impact in 38% of cases. Another option that provides a multidisciplinary approach is virtual tumor boards or case conferences, which have been pursued for testicular cancer, 11 sarcoma, 12 and lung cancer, 13 with success in improving care while overcoming geographic barriers.…”
Section: Discussionmentioning
confidence: 99%